2002
DOI: 10.1021/es011408e
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between Donor Substrates for Biologically Enhanced Tetrachloroethene DNAPL Dissolution

Abstract: Tetrachloroethene (PCE) dense nonaqueous-phase liquid (DNAPL) can act as a persistent groundwater contamination source for decades. Biologically enhanced dissolution of pure PCE DNAPL has potential for reducing DNAPL longevity as indicated previously (Environ. Sci. Technol. 2000, 34, 2979). Reported here are expanded studies to evaluate donor substrates that offer different remediation strategies for bioenhanced DNAPL dissolution, including pentanol (soluble substrate, fed continuously), calcium oleate (insolu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
121
3
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(134 citation statements)
references
References 14 publications
9
121
3
1
Order By: Relevance
“…the aqueous phase, and (ii) the transformation of PCE to compounds with higher aqueous phase solubilities (e.g., DCEs) (1). Bioenhancement of NAPL dissolution has been observed experimentally in sand column and box experiments (19,21,25). Further experiments with batch cultures have demonstrated the ability of some dechlorinating cultures to transform a mixed (PCE/tridecane) NAPL (17,26) and to achieve complete PCE-DNAPL dissolution (20).…”
Section: Form Approved Omb No 0704-0188mentioning
confidence: 89%
See 2 more Smart Citations
“…the aqueous phase, and (ii) the transformation of PCE to compounds with higher aqueous phase solubilities (e.g., DCEs) (1). Bioenhancement of NAPL dissolution has been observed experimentally in sand column and box experiments (19,21,25). Further experiments with batch cultures have demonstrated the ability of some dechlorinating cultures to transform a mixed (PCE/tridecane) NAPL (17,26) and to achieve complete PCE-DNAPL dissolution (20).…”
Section: Form Approved Omb No 0704-0188mentioning
confidence: 89%
“…Several studies with pure cultures (see Table S1, Supporting Information) and with mixed dechlorinating consortia (e.g., [17][18][19][20][21][22][23][24] have shown that bacterial PCE dechlorination occurs at or near saturated PCE concentrations. For instance, Desulfuromonas michiganensis strain BB1 was reported to dechlorinate at saturated PCE concentrations and to grow in the presence of PCE DNAPL (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The rate of dissolution from a nonaqueous phase has been studied in laboratory experiments (Powers et al, 1994), and in numerical studies at the pore scale (Dillard and Blunt, 2000;Held and Celia, 2001) and field scale Zhu and Sykes, 2000;Dillard et al, 2001). Our knowledge of multicomponent field-scale dissolution influenced by biodegradation is limited (Khachikian and Harmon, 2000) although recent studies have examined this issue in column experiments (Seagren et al, 1993;Yang and McCarty, 2002).…”
Section: Introductionmentioning
confidence: 99%
“…• Electron donors scarceness (Yang and McCarty, 2002;Aulenta et al, 2006;: It may be bypassed by the addiction of organic biodegradable substrates. Molecular hydrogen is the most important electron donor in reductive dehalogenation processes and its generation in situ remediation processes is usually due to the degradation of organic substrates, thus defined indirect electron donors, by means of fermentative processes.…”
Section: Introductionmentioning
confidence: 99%